PENGEMBANGAN PROGRAM KESEHATAN MASYARAKAT BERBASIS KELUARGA UNTUK MENINGKATKAN STATUS GIZI BALITA DI WILAYAH KERJA PUSKESMAS AMURANG BARAT - Ake Langingi; Risca Manoppo; Gledys Tirsa Lengkong; Grace Irene Viodyta Watung; James Komaling; Stella Rasu; Yuliana Delfina Rahail; Zefania Ireyne Pagayang; Dalia Novitasari; Linnie Pondaag (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Malnutrition in the under-five years can result in failure to thrive due to chronic malnutrition, as well as impaired cognitive development that impacts learning ability and future productivity. Families play an important role in the nutritional needs of children under five. The approach taken is through improving family-based public health programs. The proposed solutions include an approach to improving family health education in the context of fulfilling toddler nutrition, monitoring and mentoring toddlers, and building partnerships with cross-sector support. The findings on the results of this activity are an increase in family knowledge and awareness about the importance of fulfilling balanced nutrition in toddlers as seen in the pre and post results conducted by the PKM team which provides an assessment through observations and assistance about knowledge and awareness of the importance of fulfilling balanced nutrition. Family involvement in monitoring the growth and development of toddlers through posyandu activities and family-based health programs has increased, which is clearly seen from visits to the posyandu. Recommendations for the government, in this case the West Amurang Health Center, to be more active in carrying out assistance activities for parents related to the fulfillment of toddler nutrition. It is necessary to develop family-based public health programs to improve the nutritional status of toddlers in the West Amurang Health Center Working Area